Genetic improvement of crops using TILLING - Till, Bradley J. (Henry Stewart Talks, 2019)
Historical background on using mutagenesis to increase genetic diversity, Mutation discovery technologies, Reverse-genetic techniques, Forward genetic screens, TILLING (Targeting Induced Local Lesions IN Genomes), Examples of TILLING in crops, Next generation sequencing technologies for TILLING, Next generation sequencing technologies for forward genetics